Antibody persistence after pneumococcal conjugate vaccination in patients with chronic lymphocytic leukemia - Vesa Lindström; Janne Aittoniemi; Urpu Salmenniemi; Helena Käyhty; Heini Huhtala; Maija Itälä-Remes; Marjatta Sinisalo (Taylor & Francis Group, 2018)
Patients with chronic lymphocytic leukemia (CLL) are at a high risk for infections caused by Streptococcus pneumoniae. A pneumococcal conjugate vaccine (PCV) can induce a significant antibody response for some CLL patients. In this study we investigated antibody persistence after PCV7 in patients with CLL. The study material comprised 24 patients with CLL and 8 immunocompetent controls. The median antibody concentrations five years after PCV7 were lower for six pneumococcal serotypes in patients with CLL compared to controls, but the difference was not statistically significant. Depending on the serotype, the percentage of the CLL patients with antibody levels suggested to provide protection against invasive pneumococcal disease (IPD) varied from 29 to 71% five years after vaccination. This data suggests that PCV could result in antibody persistence at least five years in CLL patients.